101 Formulaic Alphas. Issue 84 (July 2016) - Kakashadze, Zura
Abstract : We present explicit formulas – that are also computer code – for 101 real‐life quantitative trading alphas. Their average holding period ranges from approximately 0.6 to 6.4 days. The average pairwise correlation of these alphas is low, at 15.9 percent. The returns are strongly correlated with volatility, but have no significant dependence on turnover, directly confirming an earlier result based on a more indirect empirical analysis. We further find empirically that turnover has poor explanatory power for alpha correlations.